Sustainability, cultural heritage, tourism and participation. Guidelines for the management of an indigenous people in Argentina - Giacomasso, María Vanesa (2021)
Sustainability in the province of San Luis (Argentina), centered on the safeguarding of cultural heritage, has been part of the objectives of the political agenda since the beginning of the 21st century. In this framework, the indigenous populations played a central role, for whom land restitution and housing construction programs were carried out in order to promote their cultural reactivation. In this context, through a qualitative study based on conducting interviews, participant observations and a survey of documentary sources, the case of construction of “Pueblo Ranquel” is analyzed, a settlement of Rankülches indigenous families inaugurated in 2009, which was activated Mainly from government sectors for the development of tourism, to the detriment of community involvement. This analysis concludes on the importance of participation in cultural policies and proposes methodological guidelines for participatory and sustainable management.